2021
DOI: 10.4085/1062-6050-0739.20
|View full text |Cite|
|
Sign up to set email alerts
|

Changes in the Health of Adolescent Athletes: A Comparison of Health Measures Collected Before and During the COVID-19 Pandemic

Abstract: Context: In the spring of 2020, schools closed to in-person teaching and sports were cancelled to control the transmission of CoVID-19. The changes that took place to the physical and mental health among young athletes during this time remain unknown, however. Objective: Identify changes in the health (mental health, physical activity and quality of life) of athletes that occurred during the CoVID-19 pandemic. Design: Cross-sectional study. Setting: Sample recruited… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 59 publications
(94 reference statements)
9
44
0
Order By: Relevance
“…We found that youth long-distance runners' motivation, motives, sleep duration and quality, quality of food consumed, running socialization, and anxiety were mostly negatively impacted by COVID-19 social distancing restrictions. These changes are consistent with other reported findings in youth athletes (McGuine et al, 2020 , 2021 ) and could have implications for the health and well-being of youth long-distance runners, which requires further investigation.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We found that youth long-distance runners' motivation, motives, sleep duration and quality, quality of food consumed, running socialization, and anxiety were mostly negatively impacted by COVID-19 social distancing restrictions. These changes are consistent with other reported findings in youth athletes (McGuine et al, 2020 , 2021 ) and could have implications for the health and well-being of youth long-distance runners, which requires further investigation.…”
Section: Discussionsupporting
confidence: 92%
“…Within the context of these limitations, this study adds to the current literature regarding the negative effects that large-scale cancellation of a sports had on youth long-distance runners during the COVID-19 pandemic (McGuine et al, 2020 , 2021 ). Youth long-distance runners experienced changes in motivation, lower enjoyment of running, changes in wellness, and more anxiety even though they were not necessarily restricted in their ability to run, only the context and reasons for which they participated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the limitations, the data were retrospectively collected through a self-administered online questionnaire, thus providing possible concerns about the data quality. We recognise this limitation, which was also discussed in other studies using similar surveys [45,[47][48][49][50].…”
Section: Discussionmentioning
confidence: 61%
“…Youth athletes, in particular, may have been negatively affected by the cancellation of school and sports [9]. A previous study reported that, among youth athletes, the sleeping time was higher, and the frequency of practice was lower during the pandemic compared with before the pandemic [10].…”
Section: Introductionmentioning
confidence: 99%